Kinetics of Extraction of Arabica Coffee Bean (Coffea arabica) - Lailatul Fatma; Nabilah Lu’aili Fauziah; Boy Arief Fachri; Zuhriah Mumtazah; Helda Wika Amini (University of Jember, 2024)
Coffee beans are the seeds of the coffee plant and a source of coffee beverages. Arabica coffee beans contain oil, which has many benefits. Extracting oil (solute) from coffee can be done through solvent extraction (leaching). The coffee bean oil extraction process uses n-hexane as a solvent because it can dissolve compounds with the same properties. This research aimed to study the extraction of essential oil from Arabica coffee beans and determine the kinetic model of extraction of essential oil from Arabica coffee beans by leaching. The process of separating coffee oil and solvent using thermogravimetric analysis with a temperature of 80 ℃ until the sample mass is constant. The variables used were temperature and time. The extraction time is 2 hours, with retrieval time every 10 minutes. The temperature used is 30, 40, and 50 ℃ with a ratio of material and solvent 1:10. The results showed that the kinetics of arabica coffee extraction followed the second-order extraction kinetics model. The second-order kinetic parameter values of arabica coffee essential oil extraction, namely extraction capacity (Cs) at 30, 40, and 50 ℃ were 5.45836, 5.46, and 5.46001 g L-1, respectively, the rate of the initial extraction (h) was 0.00762718, 0,00756716, and 0,0104452 gL-1minute-1, the extraction rate constant (k) was 0.000256, 0.000254, and 0.00035 g-1L-1minute-1, and determination values (R square) of 0.9965, 0.9967 and 0.9983.